Finite Element Modelling of Concrete Filled Steel Tubular Columns - Thakur, Arvind (My University, 2014)
To model the complex behaviour of concrete filled steel tubular columns (CFST) analytically in its non-linear zone is difficult. This has led engineers in the past to rely heavily on empirical formulas which were derived from numerous experiments for the design of concrete filled steel tubular columns. The Finite Element method makes it possible to take into account non-linear response. The FE method is an analytical tool which is able to model composite structures and is able to calculate the non-linear behaviour of the structural members. For structural design and assessment of composite structures, the non-linear finite element (FE) analysis has become an important tool. The method can be used to study the behaviour of reinforced, pre-stressed concrete structures and concrete filled steel tubes i.e. composite structures including both force and stress redistribution. The Finite Element method allows complex analysis of the nonlinear response of concrete filled steel tubular column to be carried out in a routine fashion. FEM helps in the investigation of the behaviour of the structure under different loading conditions and its load deflection behaviour. In the present study, the non-linear response of concrete filled steel tubular column using FE Modelling under the axial loading has been carried out with the intention to investigate the relative importance of several factors in the non-linear finite element analysis of concrete filled steel tubular columns. These include the variation in load displacement graph and the crack patterns of concrete filled steel tubular columns. Finally results from FEM compared with experimental results and comparative study shows the behaviour of concrete filled steel tubular columns under axial loading.
ME,CED, Dissertation
Keywords: CFST; concrete; steel; finite; civil engineering